SPE Annual Technical Conference and Exhibition 2003
DOI: 10.2118/84079-ms
|View full text |Cite
|
Sign up to set email alerts
|

Streamline-based Production Data Integration Under Realistic Field Conditions: Experience in a Giant Middle-Eastern Reservoir

Abstract: In this paper we apply the streamline-based production data integration method to condition a multimillion cell geologic model to historical production response for a giant Saudi Arabian reservoir. The field has been under peripheral water injection with 16 injectors and 70 producers. There is also a strong aquifer influx into the field. A total of 30 years of production history with detailed rate, infill well and reperforation schedule were incorporated via multiple pressure updates during streamline simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
5
19
0
Order By: Relevance
“…No permeability enhancements were observed in the lower interval that represents low quality reservoir. These changes are consistent with those observed by Qassab et al 29 and were found to be geologically realistic. Fig.…”
Section: A Giant Middle-eastern Field Examplesupporting
confidence: 92%
See 2 more Smart Citations
“…No permeability enhancements were observed in the lower interval that represents low quality reservoir. These changes are consistent with those observed by Qassab et al 29 and were found to be geologically realistic. Fig.…”
Section: A Giant Middle-eastern Field Examplesupporting
confidence: 92%
“…The field has been under waterflood for the last 30 years. A detailed history matching of the water flood production response using streamline models was presented by Qassab et al 29 Here we repeat the exercise using a commercial finitedifference simulator and the generalized travel-time inversion. The initial geologic model was created based on well log derived porosity, facies information and 3-D seismic data.…”
Section: A Giant Middle-eastern Field Examplementioning
confidence: 99%
See 1 more Smart Citation
“…The streamline trajectories are based upon a single forward simulation, which can be from either a streamline or a finite-difference simulator. The GTTI history matching approach has been utilized in a large number of field applications (Cheng et al 2004;Hohl et al 2006;Qassab et al 2003;Rey et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The GTTI history matching technique has been applied in a large number of field cases with two-phase oil-water flow (Qassab et al, 2003;Cheng et al, 2004;Hohl et al, 2006) and more recently to three-phase and compressible conditions (Cheng et al, 2006). Oyerinde et al (2007) reported the difficulties in the calculation of the 'optimal' time shift in the presence of non-monotonic production profiles, particularly for the gas-oil ratio at the wells.…”
Section: Introductionmentioning
confidence: 99%